Factors of Design Errors in Construction Project (A Review) - Dedy Farhan Fuadie; Yani Rahmawati; Christiono Utomo (IPTEK Journal of Proceedings Series, 2017)
Design is an important step in construction project. Errors in design cause failure in construction stage as well as the project development. Misunderstandings of design concept between parties lead to design errors that able to decrease the quality of construction works, and also cause cost overruns and project delays. Design errors also contribute to engineering failures, which can result in accidents and loss of life. Preventive actions in reducing the errors are necessary. In accordance with these issues, this research is conducted with main purpose to identify the causal factors of design error. Review to previous studies with main topic of design error was taken in order to identify the causal factors. The factors were then validated in an oil and gas industry through observation in design process and also interview to parties whom have experiences in design process. Based from research, it is found that there are 5 main causal factors. The factors are man, method, material, machine, and environment. There are also several factors that are less in accordance with the conditions in the field such as cognitive dissonance, competitive tendering, and adversarial attitudes. By knowing the cause of the design error, can be done to prevent the effort of guarantee project sustainability.